2017
DOI: 10.1038/bjc.2017.266
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic plasma microRNAs are biomarkers for prognosis and early detection of recurrence in colorectal cancer

Abstract: Background:Plasma microRNAs (miRNAs) are promising non-invasive biomarkers for colorectal cancer (CRC) prognosis. However, the published studies to date have yielded conflicting and inconsistent results for specific plasma miRNAs.Methods:We have conducted a study using robust assays to assess a panel of nine miRNAs for CRC prognosis and early detection of recurrence. Plasma samples from 144 patients in a prospective CRC cohort study were collected at diagnosis, 6, 12, and 24 months after diagnosis. miRNAs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…They identified markers of inflammation in VAT, which supports prior evidence regarding the role of visceral adiposity and cancer (31). Ristau and Yuan and colleagues have also investigated miRNAs as prognostic biomarkers (33,49). We evaluated DNA methylation patterns, for example in relation to health behaviors (30,50) and contributed to a study that showed the potential of fecal microbiota for early-stage detection of colorectal cancer (34).…”
Section: Resultssupporting
confidence: 65%
“…They identified markers of inflammation in VAT, which supports prior evidence regarding the role of visceral adiposity and cancer (31). Ristau and Yuan and colleagues have also investigated miRNAs as prognostic biomarkers (33,49). We evaluated DNA methylation patterns, for example in relation to health behaviors (30,50) and contributed to a study that showed the potential of fecal microbiota for early-stage detection of colorectal cancer (34).…”
Section: Resultssupporting
confidence: 65%
“…In the third study, miR-29a showed promising prognostic significance and could discriminate patients with recurrence from those without recurrence with an AUC of 0.703 (95% CI 0.562, 0.845). Meanwhile, in this study, preoperative high plasma miR-29a levels were associated with increased recurrence risk (HR 2.61; 95% CI 1.34-5.07; P < 0.005) [40].…”
Section: Recurrence Prediction Value Of Mir-29 and The Combination Mamentioning
confidence: 45%
“…After manually screening the titles, abstracts and keywords and then checking the full texts, 9 articles involving 10 studies for individual miR-29 and 5 articles containing 6 studies for miRNA combination markers based on miR-29 that met the inclusion norm were finally selected for the diagnostic meta-analysis while six publications including eight studies evaluating the survival outcome were identified eligible in the prognostic meta-analysis [27][28][29][30][31][32][33][34][35][36][37][38][39]. Moreover, three studies assessed the roles of miR-29 and miRNA combination markers in the recurrence prediction of CRC and one study evaluated the biomarker role in the metastasis prediction in CRC [40][41][42][43]. The characteristics of the eligible studies were summarized in Tables 1, 2 and 3.…”
Section: Study Identification and Characteristics Of Included Studiesmentioning
confidence: 99%
“…For instance, we observed significant interactions between miR-29a/b/c and collagens (COL1A1, COL2A1, COL4A1/2, COL5A1/2/3), laminins (LAMA2, LAMC2) and integrins (ITGA6, ITGB1). Recent studies have shown a critical involvement of miR-29, which was demonstrated as a prognostic marker in colon cancer, in the regulation of ECM related gene expression homeostasis [48,49]. On the other hand, tumor cells cultivated in a 3D environment exhibit differential expression of integrins due to diminished cell contact with the surface [50,51].…”
Section: Discussionmentioning
confidence: 99%